Faktor-faktor yang mempengaruhi nelayan menjual hasil tangkapan di luar perusahaan PPS KENDARI - Safitri, Nurul; Riani, Irdam; Kamri, Syamsul; Mansyur, Akhmad; Risfandi (Universitas Halu Oleo, 2023)
This study aims to determine the factors that influence fishermen to sell their fish catch in outside of the Kendari PPS company. The population in this study were fishermen who sold their catch within the Kendari PPS company and outside the Kendari PPS company totaling 80 vessels with a size of 30 GT, sampled by accidental sampling to meet 35 respondents. The data collection techniques used were observation, interviews, and documentation from respondents which were then tabulated and analyzed using Multi Criteria Analysis (MCA) to achieve the research objectives. As a result, there are 6 factors that influence fishermen to sell their catch outside PPS companies, namely price, company provisions, facilities, sources of capital, completeness, and ease of access. Of the six factors, the price difference indicator appears as the most dominant factor influencing. Thus to be able to meet the number of fishermen who sell outside PPS, the main variable that needs to be considered is the occurrence of price differences.